Recommendations for the development, implementation, and reporting of control interventions in efficacy and mechanistic trials of physical, psychological, and self-management therapies: the CoPPS Statement - Hohenschurz-Schmidt, David; Vase, Lene; Scott, Whitney; Annoni, Marco; Ajayi, Oluwafemi K.; Barth, Jürgen; Bennell, Kim; Berna, Chantal; Bialosky, Joel; Braithwaite, Felicity; Finnerup, Nanna B.; Williams, Amanda C. de C.; et al. (The BMJ, 2023)
Control interventions (often called “sham,” “placebo,” or “attention controls”) are essential for studying the efficacy or mechanism of physical, psychological, and self-management interventions in clinical trials. This article presents core recommendations for designing, conducting, and reporting control interventions to establish a quality standard in non-pharmacological intervention research. A framework of additional considerations supports researchers’ decision making in this context. We also provide a reporting checklist for control interventions to enhance research transparency, usefulness, and rigour.